2019
DOI: 10.3389/fneur.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Study of Progressive Micrographia in Parkinson's Disease

Abstract: Progressive micrographia is decrement in character size during writing and is commonly associated with Parkinson's disease (PD). This study has investigated the kinematic features of progressive micrographia during a repetitive writing task. Twenty-four PD patients with duration since diagnosis of <10 years and 24 age-matched controls wrote the letter “ e ” repeatedly. PD patients were studied in defined off states, with scoring of motor function on the Unified Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…We decided to use our own criteria for PM because we could not detect PM in the free writing by using Kim et al's criteria, even though there were PD patients with PM whose B value (by Kim et al's definition) was greater than the mean −2 SD of that of the HCs (Figure 1; Kim et al., 2005). The prevalence of PM in free writing in the current study was naturally higher than that in Kim et al's study, almost the same as that in McLennan et al's study, but lower than those in Shukla et al's (51.5%) and Zham et al's (66%) studies (Kim et al., 2005; McLennan et al., 1972; Wagle Shukla et al, 2012; Zham et al, 2019). In Shukla et al's and Zham et al's studies, the authors used the English letters, and the subjects were required to write a single letter twenty times on a paper.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We decided to use our own criteria for PM because we could not detect PM in the free writing by using Kim et al's criteria, even though there were PD patients with PM whose B value (by Kim et al's definition) was greater than the mean −2 SD of that of the HCs (Figure 1; Kim et al., 2005). The prevalence of PM in free writing in the current study was naturally higher than that in Kim et al's study, almost the same as that in McLennan et al's study, but lower than those in Shukla et al's (51.5%) and Zham et al's (66%) studies (Kim et al., 2005; McLennan et al., 1972; Wagle Shukla et al, 2012; Zham et al, 2019). In Shukla et al's and Zham et al's studies, the authors used the English letters, and the subjects were required to write a single letter twenty times on a paper.…”
Section: Discussionsupporting
confidence: 57%
“…We decided to use our own criteria for PM because we could not detect PM in the free writing by using Kim et al's criteria, even though there were PD patients with PM whose B value (by Kim et al's definition) was greater than the mean −2 SD of that of the HCs (Figure 1; Kim et al, 2005). The prevalence of PM in free writing in the current study was naturally higher than that (Kim et al, 2005;McLennan et al, 1972;Wagle Shukla et al, 2012;Zham et al, 2019 In the current study, the prevalence of PM in the free writing task was 10% in the HC group, and there was no significant difference in the Corrected B values or the prevalence of PM in the free writing task between the PD and HC groups. In addition, if we did not set the cutoff value of the corrected B value at the mean −1.5 SD of that of the HCs, the prevalence of PM in the free writing task would have been 25% in the PD group and 20% in the HC group.…”
Section: Experimental Writing Testsmentioning
confidence: 63%
See 1 more Smart Citation
“…Independent sample t-test was performed to compare PD and control groups to confirm age-matching, while Chi-Square test was performed for differences in gender and handedness (10).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a ‘typical' historical script size is one limitation, since writing size varies considerably in a normal subject depending on writing context ( 9 ). In a previous study, we found that classifications of consistent micrographia based on letter size did not yield a distinct subset ( 10 ). Only 4% had a purely consistent pattern, while some PD patients with decrement also fell below the consistent cut-off.…”
Section: Introductionmentioning
confidence: 89%